2015
DOI: 10.1089/ars.2013.5757
|View full text |Cite
|
Sign up to set email alerts
|

The Use of microRNAs to Modulate Redox and Immune Response to Stroke

Abstract: Significance: Cerebral ischemia is a major cause of death and disability throughout the world, yet therapeutic options remain limited. The interplay between the cellular redox state and the immune response plays a critical role in determining the extent of neural cell injury after ischemia and reperfusion. Excessive amounts of reactive oxygen species (ROS) generated by mitochondria and other sources act both as triggers and effectors of inflammation. This review will focus on the interplay between these two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 210 publications
1
36
0
Order By: Relevance
“…Several recent studies have shown the regulatory role of miRNA on redox systems176, 177. However, such a role in the field of cancer MDR has not been fully studied.…”
Section: Aberrant Expression Of Mirnas and Cancer Drug Resistancementioning
confidence: 99%
“…Several recent studies have shown the regulatory role of miRNA on redox systems176, 177. However, such a role in the field of cancer MDR has not been fully studied.…”
Section: Aberrant Expression Of Mirnas and Cancer Drug Resistancementioning
confidence: 99%
“…miRNAs bind to messenger RNAs (mRNAs), known as their targets, based on sequence complementarity and direct the degradation or repression of translation of the targeted mRNAs. Recent evidence increasingly supports a role for miRNAs in response to cerebral ischemia, as we have reviewed recently (Ouyang et al, 2013a; Ouyang et al, 2013b). Numerous miRNAs target BCL-2 family proteins.…”
Section: Introductionmentioning
confidence: 81%
“…The most common mechanism is for miRNAs to bind to messenger RNAs (mRNAs), known as their targets, based on sequence complementarity and direct the degradation or repression of translation of the targeting mRNAs. Recent evidence increasingly supports a role for miRNAs in response to cerebral ischemia, as we have reviewed recently (Ouyang et al, 2013b; Ouyang et al, 2013a). The fast post-transcriptional effect of miRNAs, and their ability to simultaneously coordinate regulation of many target genes, suggests that miRNAs may have greater therapeutic potential as candidates for the treatment of stroke than therapies targeting a single gene by direct transcriptional control.…”
Section: Introductionmentioning
confidence: 81%
“…Recently, miR-181a was shown to directly target molecular chaperone GRP78 (Ouyang et al, 2012b), anti-apoptotic members of the BCL2 family BCL2 and myeloid cell leukemia (MCL) 1 (Ouyang et al, 2012a), and X-linked inhibitor of apoptosis (XIAP) (Hutchison et al, 2013) as well as some target proteins involved in controlling mitochondrial function, redox state, and inflammatory pathways (for recent reviews see Ouyang and Giffard (2013); Ouyang et al (2013b)). Although miR-181a antagomir reduces miR-181a levels and significantly inhibits the decrease of GLT-1 after forebrain ischemia, miR-181a does not directly target GLT-1 (Moon et al, 2013).…”
Section: Astrocyte-enriched Mirnas As Potential Targets For Protecmentioning
confidence: 99%